Dostoevsky : Language, Faith, and Fiction - Williams, Rowan, 1950- (Book collections on Project MUSE., 2008)
"Rowan Williams explores the intricacies of speech, fiction, metaphor, and iconography in the works of one of literature's most complex and most misunderstood, authors. Williams' investigation focuses on the four major novels of Dostoevsky's maturity (Crime and Punishment, The Idiot, Devils, and The Brothers Karamazov). He argues that understanding Dostoevsky's style and goals as a writer of fiction is inseparable from understanding his religious commitments. Any reader who enters the rich and insightful world of Williams' Dostoevsky will emerge a more thoughtful and appreciative reader for it."--Jacket.